Race, ethnicity and law - Deflem, Mathieu (Bingley : Emerald Publishing Limited, 2017)
This new volume of Sociology of Crime, Law and Deviance addresses issues of race and ethnicity within the law and law-related phenomena. Even in today's so-called multicultural, post-racial world racial and ethnic concerns prevail in many aspects of modern law. Contributors to this volume examine racial and ethnic disparities in sentencing and punishment; the continued problematic nature of the African American experience within the US system; the criminalization of immigrants; racial inequities in the administration of drug laws; and the racial disparities that affect juvenile justice. This volume will be of interest to students and researchers in law, socio-legal studies, criminology, criminal justice, sociology and public policy.
Prelims -- Introduction: the laws of race, ethnicity and law -- Law and black lives -- Disparities in sentencing and punishment -- Systems and mechanisms of inequality -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Social Science -- Criminology; Law & society; Criminology; Social sciences